Platelet‐derived extracellular vesicles released after trauma promote hemostasis and contribute to DVT in mice. (28th July 2019) - Dyer, Mitchell R.; Alexander, Wyeth; Hassoune, Adnan; Chen, Qiwei; Brzoska, Tomasz; Alvikas, Jurgis; Liu, Yingjie; Haldeman, Shannon; Plautz, Will; Loughran, Patricia; Li, Hui; Boone, Brian; et al.
Abstract: Background: Traumatic injury can lead to dysregulation of the normal clotting system, resulting in hemorrhagic and thrombotic complications. Platelet activation is robust following traumatic injury and one process of platelet activation is to release of extracellular vesicles (PEV) that carry heterogenous cargo loads and surface ligands. Objectives: We sought to investigate and characterize the release and function of PEVs generated following traumatic injury. Methods: PEV content and quantity in circulation following trauma in humans and mice was measured using flow cytometry, size exclusion chromatography, and nanoparticle tracking analysis. PEVs were isolated from circulation and the effects on thrombin generation, bleeding time, hemorrhage control, and thrombus formation were determined. Finally, the effect of hydroxychloroquine (HCQ) on PEV release and thrombosis were examined. Results: Human and murine trauma results in a significant release of PEVs into circulation compared with healthy controls. These PEVs result in abundant thrombin generation, increased platelet aggregation, decreased bleeding times, and decreased hemorrhage in uncontrolled bleeding. Conversely, PEVs contributed to enhanced venous thrombus formation and were recruited to the developing thrombus site. Interestingly, HCQ treatment resulted in decreased platelet aggregation, decreased PEV release, and reduced deep vein thrombosis burden in mice. Conclusions: These data demonstrate that trauma results in significant release of PEVs which are both pro‐hemostatic and pro‐thrombotic. The effects of PEVs can be mitigated by treatment with HCQ, suggesting the potential use as a form of deep vein thrombosis prophylaxis.